Emergency maternal referral worksheet as a clinical decision-making tool - Mochammad Hud Suhargono (Universitas Airlangga, 2021)
Objective: This study aimed at discovering some different delivery outcomes from maternal emergency referral cases in referral health facilities (RHF) for those who used did not use Emergency Maternal Referral Worksheet (EMRW) at public health facilities (PHF). Materials and Methods: This study was a quantitative research with observational case control. It used in-depth interviews to several health centers in Tuban by using Mann Whitney statistic test. Results: The results of statistical test Mann Whitney, 161 referral cases were found to have p value of 0.036. It indicated significant differences in delivery outcomes. The differences were found in groups of mothers in mortality, high morbidity, and survived groups who used and did not use EMRW. Supporting and resisting factors from 22 respondents examined were socialization and technical support, leadership and supervision by the heads of PHF and Regional Health Ministry, as well as coordination and synergy among policy makers and related parties. Conclusion: The use of EMRW affects the outcome of patients so that EMRW can be used as a clinical decision making tool in other maternal and non-maternal health services.